The value relevance of financial instruments and the impact of corporate governance mechanisms / Syed Khusairi Tuan Azam - Tuan Azam, Syed Khusairi (2013)
This study is conducted to examine the value relevance of fair value for financial assets upon the adoption of FRS 139 Financial instruments on recognition and measurement in Malaysia. Previously, information relating to financial instruments only needs to be disclosed in the notes to the financial statements. Upon the adoption of FRS 139, the financial instruments need to be recognised in the statement of financial position. The sample for this study consists of top 200 companies listed on Bursa Malaysia and information relating to financial assets in year 2010 and 2011 was extracted from the annual report. This study finds the recognition of fair value for financial instrument is value relevance in year 2011 but not in year 2010. In addition, this study also provides evidence that show the corporate governance mechanism does influence the value relevance of fair value for financial assets. The increase in audit committee meeting shows significant negative association for value relevance of fair value financial instrument in year 2011 but not in year 2010. Meanwhile, the result for size of audit engagement was negatively significant in both years. However, the present study finds no evidence that show significant association between board independence and measurement of fair value financial assets.